The Contribution of Records Personnel Towards Organizational Performance at Kabale Municipal Council. - Kiiza, Martin (Kabale University, 2023)
The study sought to assess the contributions of record of records personnel towards organizational performance at Kabale Municipal Council. The aims and objectives were to establish the contributions made by records personnel on organizational performance in Kabale Municipal Council, to identify the factors affecting records management and organizational performance at Kabale Municipal Council, to suggest the strategies that could enhance the contributions of records personnel to organizational performance at Kabale Municipal Council. The study was guided with the current approaches to records management systems on organization performance because sufficient attention is paid to records management by records personnel. The literature review maintains that records personnel plays a big role in management of records and anchor on a written records management policies, standards and procedures. The researcher used a case study research design where Kabale Municipal Council registry was chosen for this study. The population of the research comprised of staff members of the registry and other few stake holders at Kabale Municipal Council, a sample of (23) people were elected through a simple random sampling procedure to gather information following research tools were used: interview guide and questionnaire were used, the results indicated that records personnel were not sensitized about the new records systems which can be used to manage records systematically, the researcher recommended that the registry should develops a records management system, train its staff on simple records management standards, adopts a records preservation plan, revive the records office and to appraise and dispose records systematically.